Politisasi Agama di Tahun Politik: Politik Pasca-Kebenaran di Indonesia dan Ancaman bagi Demokrasi - Kurniawan, Budi (Jurnal Sosiologi Agama, 2018)
This paper analyzes the politicization of religion that occurred in Indonesia, especially in the current political year. Ahead of the 2018 electoral election and the 2019 presidential election, religious sentiments are often used for pragmatic political interests. An example is reflected on 2019 Ganti Presiden Movement. In the context of post-truth politics, feelings and opinions influence the discourse of public politics more than objective facts. In other words, the line between facts and opinions is blurred. Hoax, opinions, and distortions of fact dominate the existing political discourses. This paper uses a sociological approach to analyzing post-truth political phenomena in Indonesia as reflected in recent cases of politicization of religion. The paper also provides a brief overview of some popular data and facts in actual political discourse as evidence of disinformation. However, the politicization of religion reflects unhealthy democratic conditions. Issues of religion in Indonesian context is sensitive and prone to be the trigger of conflict. This paper asserts that the politicization of religion in the post-truth era must be addressed critically and seriously, so that the climate of democracy in Indonesia can be well preserved. Keyword: Politicization of religion, 2019 ganti presiden, Post-truth, Democracy